Redescription of the African Chordodes albibarbatus Montgomery 1898, and description of Chordodes janovyi n. sp. (Gordiida, Nematomorpha) and its non-adult stages from Cameroon, Africa - Bolek, Matthew G.; Schmidt-Rhaesa, Andreas; Hanelt, Ben; Richardson, Dennis J. (Zootaxa, 2010)
We redescribe Chordodes albibarbatus Montgomery 1898 from the original holotype male and the originally described female specimen using Nomarski interference contrast microscopy. Our reinvestigation indicates that C. albibarbatus is sexually dimorphic and contains five types of areoles in the male and six types of areoles in the female. Our reinvestigation of C. albibarbatus indicates that it is a distinct species, and is most similar to the African Chordodes gariazzi Camerano 1902 and Chordodes heinzei Sciacchitano 1937, all of which share simple “blackberry”, bulging, tubercles, and thorn areoles. In addition, we describe adult free-living male and female Chordodes janovyi n. sp. collected from West Province, Cameroon, Africa using both morphological (light and scanning electron microscopy) and molecular data, and designate types for this species. Chordodes janovyi belongs to a large group of Chordodes in which simple areoles are smooth or superficially structured less so than “blackberry” areoles. Present among the simple areoles are clusters of crowned and circumcluster areoles along with thorn and tubercle areoles, whereas bulging areoles are absent. We also describe the egg strings, eggs, larvae, cysts, and oviposition behavior of C. janovyi and compare these non-adult life stages to other nematomorph genera and species for which such life cycle stages are known, and we discuss the use of non-adult stages and the use of molecular tools in future studies of nematomorph systematics and biodiversity.